539 The role of rehabilitation and anabolic treatment in severe osteoporosis associated with significant vitamin D deficiency – case report (Balneo and PRM Research Journal, 2024)
Abstract: It is well known that vitamin D deficiency increases the risk of osteoporosis andthat vertebral compressions fractures are a manifestation of osteoporosis. This paperpresents the case of a patient with severe osteoporosis associated with vitamin Ddeficiency who developed over the course of two years multiple vertebral compressionfractures. Method: We present the case of a 76‐year‐old caucasian female diagnosed withosteoporosis and significant vitamin D deficiency who was investigated for mechanicalpain and functional deficit at the level of the spine and walking disorders. The patient washospitalized in our Rehabilitation department twice. At the first hospitalization two yearsago, the deficiency of vitamin D was found and the treatment was initiated. During thesecond hospitalization, biochemical and radiological investigations were per‐formed to establishthe diagnosis. Numerous vertebral compression fractures were dis‐covered which were not re‐vealed in the imaging investigations performed two years earli‐er. She underwent symptomatic andappropriate medical rehabilitation treatment. Results and discussion: The evolution was favorableafter the hospitalization period, with a decrease in pain and functional deficit, as well as walkingimprovement. After endocrinological consultation it was decided to initiate therapy with Teripar‐atide which can decrease the risk of future fractures and reduce the back pain. Conclusions: Ade‐quate and prompt treatment of vitamin D deficiency and osteoporosis is very important to avoidvertebral compression fractures or other complications of this disease. Physical and rehabilitationmedicine also plays an important role in management of these patients.Keywords: osteoporosis, vitamin D deficiency, vertebral compression, teriparatide